Niche divergence at the intraspecific level in an endemic rare peony (Paeonia rockii): A phylogenetic, climatic and environmental survey - Dong, Peng-Bin; Wang, Ling-Juan; Jia, Yun; Li, Zhong-Hu; Wang, Hong-Yan; Guo, Feng-Xia; Chen, Yuan (Frontiers in Plant Science, 2022)
Ecological factors have received increasing attention as drivers of speciation but also in the maintenance of postspeciation divergence. However, the relative significance of the responses of species to climate oscillations for driving niche divergence or conservatism in the evolution of many species that pass through diverse environments and limited geographical boundaries remains poorly understood. Paeonia rockii (one of the ancient species of Paeonia) comprising two subspecies called Paeonia rockii subsp. rockii and Paeonia rockii subsp. taibaishanica is an endemic, rare, and endangered medicinal plant in China. In this study, we integrated whole chloroplast genomes, and ecological factors to obtain insights into ecological speciation and species divergence in this endemic rare peony. RAxML analysis indicated that the topological trees recovered from three different data sets were identical, where P. rockii subsp. rockii and P. rockii subsp. taibaishanica clustered together, and molecular dating analyses suggested that the two subspecies diverged 0.83 million years ago. In addition, ecological niche modeling showed that the predicted suitable distribution areas for P. rockii subsp. rockii and P. rockii subsp. taibaishanica differed considerably, although the predicted core distribution areas were similar, where the population contracted in the last interglacial and expanded in the last glacial maximum. Under the emissions scenarios for the 2050s and 2070s, the suitable distribution areas were predicted to contract significantly, where the migration routes of the two subspecies tended to migrate toward high latitudes and elevations, thereby suggesting strong responses of the distributions of the two subspecies to climate change. These findings combined with the phylogeographic relationships provide comprehensive insights into niche variation and differentiation in this endemic rare peony, and they highlight the importance of geological and climatic changes for species divergence and changes in the population geographic patterns of rare and endangered medicinal plants in East Asia.